Pengaruh Layanan COD dan Consumer Review Terhadap Keputusan Pembelian : Studi Kasus pada Pembelian Produk Wardah Cosmetics di Shopee - Fitria, Dini Irma; Jati, Dwi Astuti Sekar; Muthi’ah, Firyal Luthfi; Sofyan, Mohammad; Ayu, Renisya (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
This study aims to determine the effect of social media advertising and impulse buying on purchasing decisions for Scarlett Whitening products. This study uses a quantitative approach with a population of Scarlett Whitening consumers in Scarlett Whitening e-commerce Shopee users. The sampling technique used purposive sampling method by taking samples through questionnaires distributed online. The sample was distributed to 109 respondents according to the research criteria. Data analysis technique using multiple regression. The results of the study explained that simultaneously social media and Impulse Buying influenced the purchase decision of Scarlett Whitening Products by 64.2%. Partially, social media has a significant influence on the purchase decision of Scarlett Whitening Products by 51% and impulse buying also has a significant influence on the purchase decision of Scarlett Whitening Products by 13.2%.